Love on the Santa Fe: Under the Starry Skies - Book 3 - Peterson, Tracie (Minneapolis, Minnesota : Bethany House Publishers, a division of Baker Publishing Group, 2022)
"When an accident leaves Cassandra Barton incapacitated, she spends her time compiling a book of stories about the men working on the Santa Fe Railroad. But worry grows as revolutionaries set out to destroy the railroad. As the danger intensifies, Cassie and her longtime friend Brandon must rely on their faith to overcome the obstacles that stand in the way"--
Keywords: Women dressmakers -- Fiction; Man-woman relationship -- Fiction; Santa Fe (N.M.) -- Fiction; San Marcial (N.M.) -- Fiction; Romance fiction; Christian fiction; Novels